Influence of infertility and fertility adjustment on marital satisfaction - Ferreira, Manuela (2015)
Abstract Background: Infertility requires medical attention and treatment. It is also a disturbing life event with implications in dimensions of the individuals’ and the infertile couples’ lives (personal, relational and social). Research question: What factors influence marital satisfaction in couples with infertility problems? Objectives: Determine the influence of socio-demographic and obstetric variables, as well as personal history in the adjustment to fertility and marital satisfaction; evaluate the influence of infertility and fertility adjustment on marital satisfaction. Methods: It is a quantitative study with a 106 women being followed at the reproductive medicine unit of Center of Portugal. Data collection was through a questionnaire comprising a socio-demographic component, obstetric history, personal history and Fertility Adjustment Scale (Leal, 2010) and Evaluation Scale regarding Marital Life Satisfaction (Narciso & Costa, 1996) scales. Results: The adjustment to fertility is influenced by age and by the existence of previous pregnancies on "Total Adjustment" (p = 0,013 and p = 0,026, respectively) and by the number of services one attends, in "Life on Hold" (p = 0,024). Marital satisfaction, is influenced by education level and the beginning of infertility treatments on "Sexuality" (p = 0,039). Conclusion: In this research, it became clear that the adjustment to fertility may not influence at all marital satisfaction; however it influences very important aspects of the couple’s life. Thus, aspects of marital satisfaction will influence determinants of fertility adjustment, such as “Emotional Intimacy", "Sexuality" and "Communication/Conflict" in "Life on Hold" and "Autonomy" in "Parenting".